2013
DOI: 10.1364/oe.21.031309
|View full text |Cite
|
Sign up to set email alerts
|

Lead silicate microstructured optical fibres for electro-optical applications

Abstract: We report progress towards the realization of optical modulators based on electro-optic effects in soft glass fibres. A hybrid fabrication procedure was developed for producing microstructured lead silicate glass fibres with internal electrodes. Electro-optical characterization confirms experimentally that the enhanced nonlinear properties and superior isolation between the optical field and the electrodes make these fibres an ideal candidate platform for efficient electro-optical devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Many of these efforts were focused on control of dispersion, enhancement of the nonlinearity, reduction of the fiber transmission loss, or increase of sensitivity to environmental conditions in single-material MOFs [ 5 ]. Multi-material MOFs have also been developed for added functionality, e.g., hollow-core fibers filled with liquids [ 6 ] or gases [ 7 ] for sensing, with gases for high-power pulse compression [ 8 , 9 ] and nonlinear effects [ 10 , 11 ], with semiconductors for electronic functionality [ 12 ], and with integrated electrodes [ 13 , 14 ] and liquid crystals [ 15 ] for optical switching.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these efforts were focused on control of dispersion, enhancement of the nonlinearity, reduction of the fiber transmission loss, or increase of sensitivity to environmental conditions in single-material MOFs [ 5 ]. Multi-material MOFs have also been developed for added functionality, e.g., hollow-core fibers filled with liquids [ 6 ] or gases [ 7 ] for sensing, with gases for high-power pulse compression [ 8 , 9 ] and nonlinear effects [ 10 , 11 ], with semiconductors for electronic functionality [ 12 ], and with integrated electrodes [ 13 , 14 ] and liquid crystals [ 15 ] for optical switching.…”
Section: Introductionmentioning
confidence: 99%
“…However their initial seed pulse was at 3.5 μm which is not at the telecommunications wavelength; also the length of the fiber is longer than we used here. In [13], SC was produced in dispersion tailored all-solid soft glass photonic crystal fibers pumped at 1550 nm. However, the spectrum broadening was mainly caused by self-phase modulation and four wave mixing rather than soliton dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Microstructure fabrication technique has been widely applied to non-silica glasses [10][11][12][13][14][15][16][17][18]. Here we choose SF57 as the material for the MOF.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, low-T g glass systems exhibit moderate processing temperatures, allowing for a larger panel of potential metals to be co-drawn with. Monro et al identified tellurite glasses as being especially suitable for electro-optical fiber devices, owing to their large nonlinear coefficients and drawing ability [4,5]. Here post-drawing liquid metal injection was employed for providing optical fibers with internal electrodes.…”
Section: Introductionmentioning
confidence: 99%